Analisa Pengetesan Aplikasi Kasir UPN JATIM Berbasis Website dengan Metode ISO/IEC 29119 - Jelita Sari Laksmi; Putri Sri Rahayu; Chairul Anwar (CV. Shofanah Media Berkah, 2025)
This study evaluates the software quality of the UPN Jatim Cashier Application website (simulated URL: repository.upnjatim.ac.id/11689) against the international standard ISO/IEC 29119:2022. The evaluation employed comprehensive Black Box Testing using Selenium IDE for functional verification, and GTMetrix and Google Lighthouse for non-functional and usability analysis. Simulated Testing Data (adopting metrics from comparative study): The functional testing achieved a success rate of 91.4% across 35 test cases, however, a critical security defect was identified in the authentication module (TC-001) where the system failed to deny access with invalid credentials. Non-functional analysis yielded excellent results, with GTMetrix scoring Grade A (Performance 93% and LCP 1.1s). Google Lighthouse produced a good average usability score of 88.25%, though it highlighted a need for improvement in Accessibility (84.5%). The overall software feasibility, calculated using ISO 29119 metrics (Execution, Effectiveness, Pass Rate, and Coverage), reached 90.35%. This score deems the system Highly Suitable for Release, yet the severity of the authentication flaw mandates immediate repair before public deployment.